Influence of timing and rate of gain on puberty and reproductive performance of beef heifers - Smith, J.M.; Lamb, G.C.; Minton, J. Ernest; Brandt, Robert T., Jr.; Cochran, R.C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-seven crossbred heifers (573 lb initial body weight) were developed in drylot and limit-fed a corn, sorghum silage diet predicted to produce gains of either 1 lb/day for the entire developmental period (EVENGAIN) or .25 lb/day for the first two-thirds of the period followed by 2 lb/day during the last third (LATEGAIN). Treatments began on November 15, 1993 and continued until April 25, 1994, the onset of the breeding season. Actual daily gains averaged 1.31 lb/day for EVENGAIN heifers, whereas LATEGAIN heifers averaged .55 lb/day for the first two-thirds of the feeding period and 2.5 lb daily for the last third. Age and weigh t at puberty were not affected by feeding treatment, and body condition score, estimated fat thickness, frame score, and pelvic area were similar regardless of growth regimen. At the conclusion of the feeding period, estrus was synchronized using two injections of prostaglandin F , and heifers 2" were inseminated artificially during a 45-day breeding season. Open heifers were mated naturally for an additional 1 5 days. First-service and overall pregnancy rates were similar between treatments. In summary, rate and time of gain did not affect puberty or breeding performance. However, LATEGAIN heifers were more efficient and developed on 12% less feed than the EVENGAIN heifers. These data suggest that replacement heifers can be developed more efficiently if most of the body weight gain required to enter the breeding season occurs late in development.
Keywords: Beef; Beef heifers; Puberty; Heifer development